Learning ordinary differential equation at undergraduate level: A systematic learning review - Kurniadi, Elika; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
The research about Ordinary Differential Equation (ODE) has increased more widely since 1970. Therefore, several published articles in some journals can be found in some sources. This paper aims to provide an overview of the learning differential equation in higher education based on relevant literature. Therefore, we are interested in conducting a Systematic Literature Review (SLR) methodology from 24 articles generated from Top 5 Scopus Q1 according to SJR reported by Scimago Journal & Country Rank in the subject area of education. The present study focuses on two aspects, namely: 1) the learning method of ODE that is proposed in the academic literature, and 2) the topic of ODE has been put forward and discussed in the academic literature. The systematic literature review found four methods of learning ODE (active learning, mathematical modelling, information, and technology communication, and geometric and qualitative solutions). Moreover, we also concluded that the several topics of ODE in the academic literature are 1) first order of ODE, 2) Euler method, 3) application to the problem (rate of change, population model, logistic generalized, and spring-mass), 4) second-order of ODE, and 5) system of ODE. The result of this study can provide a summary of existing literature and identify the weakness or gap to be investigated further in the following research related to the topic of ODE.